Tree trunk volume of Shorea species case study in Darmaga and Haurbentes research forest in West Java, Indonesia - Mindawati, N.; Hendromono; Hiratsuka, M.; Toma, T.; Morikawa, Y.; Gintings, A.N. (2004)
Activities of forest management require a well planned, systematic and well directed handling, so that achieving maximal and beneficial results in terms of economic, ecological and social prospects. In relevant to data on trunk volume of available tree stands are required to set up a plan intended to produce sustainable timber. The research was conducted in the Darmaga and Haurbentes research forests of the Forest and Nature Conservation Research and Development Center located in West Java. The trunk volume model as conceived was based on the Smalian's formula employed to particular tree species (i.e. Shorea balangeran, S. guisso, S. leprosula, S. mecistopteryx, S. ovalis, S. palembanica, S. selanica, S. seminis and S. stenoptera). This model could estimate the tree trunk volume with non-destructive sampling. In this way, therefore, the trunk volume can be estimated from the tree diameter on a single variable.